Job changes and individual-job specific wage dynamics - Laura Hospido (Institute for the Study of Labor (IZA), 2010)
This paper develops an error components model that is used to examine the impact of job changes on the dynamics and variance of individual log earnings. I use data on work histories drawn from the Panel Study of Income Dynamics (PSID) that makes it possible to distinguish between voluntary and involuntary job-to-job changes. The potential endogeneity of job mobility in relation to earnings is circumvented by means of an instrument variable estimation method that also allows to control for unobserved individual-job specific heterogeneity. Once controlled for individual and job-specific effects, the persistence within jobs is almost zero, whereas across jobs is significant but small.
urn:nbn:de:101:1-201008115870
Keywords: C23; J31; 330; panel data; dynamic models; individual-job specific fixed effects; job changes; individual wages